Philibert de Naillac, Master of Rhodes: 1396‒1421 - Luttrell, Anthony (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2023)
Philibert de Naillac belonged to the nobility of Berri. He entered the military-religious order of the Hospital and by 1374 held the Commandery of Lureil in the Priory of Auvergne; in 1390 he became Prior of Aquitaine and was due to travel to Rhodes. Apparently in 1395 he again left for Rhodes where, probably on 6 May 1396, he was elected Master. Soon after he led a Hospitaller contingent into the Black Sea and up the Danube to Nikopolis to join a crusade which on 25 September 1396 was defeated by the Turks; Naillac escaped, rescuing Sigismund of Hungary from captivity or death. Subsequently the Hospitallers defended Constantinople and the Morea against the Turks, built the large “Naillac” tower in Rhodes harbour, and in 1406/1407 constructed a castle at Bodrum on the Anatolian mainland opposite Kos. Meanwhile the Hospital’s holy warfare at sea included the semi-piratical corso. Naillac’s administrative tasks and visitations were extensive in both East and West. The Hospital's manpower and money reaching Rhodes were seriously reduced by defections provoked by the papal schism, and in 1409 the Master travelled to Pisa where a council elected a new pope with Naillac guarding the conclave. He continued to work for a settlement and in 1417 he again guarded the conclave at Constance where the schism was largely ended. The schism within the Hospital itself was also slowly eliminated. In 1420 Naillac returned to Rhodes where he held a chapter general which passed important legislation. He died in 1421 after a lengthy rule which, not without some dubious aspects, did much to preserve the Hospitaller order.